Off Balance Sheet Disclosures: A Comparison Between Indian and US Companies - Bapat, Varadraj; Raithatha, Mehul (Indian Journal of Finance, 2012)
Off balance sheet items refer to an asset or debt or financing activity or financial instrument not on the company’s balance sheet, but having a potential impact on the financial position. The significance of off balance sheet items as a source of finance has been steadily increasing since 1990s. Of the Indian Accounting Standards (AS) related to off balance sheet items, AS 19 (Leases) and AS 27 (Financial Reporting of Interests in Joint Ventures) are compulsory, whereas AS 30 (Financial Instruments: Recognition and Measurements) and AS 32 (Financial Instruments: Disclosures) are recommendatory in nature. Corresponding Financial Accounting Standards (FAS) in US are - FAS 133 (Accounting for Derivative Instruments and Hedging Activities) and FAS 13 (Accounting for Leases). The paper compares the disclosure level for off balance sheet items, particularly with reference to leases, interests in joint ventures, and financial instruments, including derivatives for major Indian and US companies. Indian companies need to substantially enhance their disclosure levels for off balance sheet items in order to match the international standards. This is expected to happen once AS-30 and AS-32 become mandatory from April 1, 2011. The Indian Pharma and IT sector is more transparent in terms of their disclosures for derivatives, as compared to the auto sector. Telecom sector companies have not moved to AS 30 and continue to capitalize losses on higher percentage of foreign borrowing funded fixed assets. This has helped them to avoid showing foreign losses.